CCAFS impact assessment of national policy engagement in Kenya on uptake of climate-smart agriculture technologies and practices - Okumu, Boscow (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This study assessed the impact of engagements by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) at policy and household levels in Kenya. Specifically, the study assessed the extent to which CCAFS engagement contributed to the observed changes in terms of shaping policy and climate-smart agriculture (CSA) coordination among others. At the household level, the study assessed the factors influencing uptake of CSA practices among smallholder farmers and the subsequent impact of the CSA practices on agricultural yield, livestock holding and welfare of households. The study used a mix of qualitative and quantitative approaches. Specifically, key informant interviews, focus group discussions, observation and cross-sectional data from household interviews and a range of econometrics techniques were used to assess the impact at household level, namely, propensity score matching and instrumental variable approach.